Does resisted sled towing improve the physical qualities of elite youth soccer players of differing maturity status? - Morris, R.; Myers, T.; Emmonds, S.; Singleton, D.; Till, K. (Journal of Science in Sport and Exercise, 2021)
Purpose: Sled towing has been shown to be an effective method to enhance the physical qualities in youth athletes. The aim of this study was to evaluate the impact of a 6-week sled towing intervention on muscular strength, speed and power in elite youth soccer players of differing maturity status. Method: Seventy-three male elite youth soccer players aged 12-18 years (Pre-Peak Height Velocity [PHV] n = 25; Circa-PHV n = 24; Post-PHV n = 24) from one professional soccer academy participated in this study. Sprint assessments (10 m and 30 m), countermovement jump and isometric mid-thigh pull were undertaken before (T1) and after (T2) a 6-week intervention. The training intervention consisted of 6 weeks (2 × per week, 10 sprints over 20 m distance) of resisted sled towing (linear progression 10%-30% of body mass) during the competitive season. Bayesian regression models analysed differences between T1 and T2 within each maturity group. Results: There were minimal changes in strength, speed and power (P = 0.35-0.80) for each maturity group across the 6-week intervention. Where there were changes with greater certainty, they are unlikely to represent real effect due to higher regression to the mean (RTM). Conclusion: It appears that a 6-week sled towing training programme with loadings of 10%-30% body mass only maintains physical qualities in elite youth soccer players pre-, circa-, and post-PHV. Further research is required to determine the effectiveness of this training method in long-term athletic development programmes.